Analisis Pencatatan dan Pelaporan Belanja Langsung pada Dinas Satuan Polisi Pamong Praja Kabupaten Sarolangun - Fauziah Fauziah; Yulia Istia Ningsih (CITRA EKONOMI, 2022)
This research was conducted at the Civil Service Police Unit of Sarolangun Regency with the aim of knowing how the systems and procedures, recognition, recording and reporting of direct expenditures are at the Civil Service Police Unit of Sarolangun Regency. In analyzing the data, this research was carried out using descriptive qualitative methods. The results showed that the Recording and Reporting of Direct Expenditures at the Civil Service Police Unit of Sarolangun Regency had implemented Government Regulation No. 71 of 2010 concerning Government Accounting Standards and Minister of Home Affairs Regulation No. 64 of 2013 concerning Guidelines for State/Regional Financial Management. Expenditure reporting by the Sarolangun District Civil Service Police Unit has implemented PP No. 71 of 2010 concerning accrual-based recording, which can be seen from the recording of expenditure accounts consisting of operating expenditures including personnel expenditures and goods and services expenditures as well as capital expenditures which include equipment and machinery expenditures as well as other fixed assets expenditures.